PENERAPAN MEDIA WORDWALL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA PELAJARAN PENDIDIKAN PANCASILA MATERI PRINSIP GOTONG ROYONG DALAM KEBERAGAMAN DI KELAS X-3 SMA NEGERI 1 RANTAU SELATAN - Andriani, Dedek (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research is motivated by the low motivation and learning outcomes of students in Pancasila education subjects in class X-3 at SMA Negeri 1 Rantau Selatan. One solution that can be done is to use the Wordwall Platform media as a source of learning, media, teaching aids, and interesting assessment tools in the world of education. From the results of the analysis of class research data (PTK) using Wordwall media to increase motivation and learning outcomes in Pancasila Education Lessons on the Principles of Mutual Cooperation in Diversity in class X-3 SMA Negeri 1 Rantau Selatan, it can be concluded that there is an increase in student motivation and learning outcomes by 33% between cycles I and II with the realized completion criteria increasing from 50% to 83%. Thus, students successfully achieved the criteria of completion applied in schools, namely 75 and the success indicators made by researchers of ?80% can achieve better results indicating that by implementing Wordwall media, it can improve the motivation and learning outcomes of class X-3 students of SMA Negeri 1 Rantau Selatan.